Respiratory Emergency in Hospitalized patient with Intrathoracic Malignancy at H. Adam Malik General Hospital - Elizabeth Napitupulu; Noni Novisari Soeroso; Setia Putra Tarigan; Putri Chairani Eyanoer (Jurnal Respirologi Indonesia, 2022)
Background: Increased number of intrathoracic malignancy cases (Lung tumor, Mediastinum tumor, Secondary lung cancer and Chest wall tumor) contribute in increased complications of respiratory emergencies such as superior cava vein yyndrome (scvs), massive malignant pleura effusion (mpe), central airway obstruction (cao), massive hemoptysis, lung thromboembolism and pneumothorax. This study aims to look at the proportions, outcomes, and factors that influence respiratory emergency in intrathoracic malignancy cases.Methods: This was a retrospective case series of inpatient respiratory emergencies in patients intrathoracic malignancy at H. Adam Malik Central General Hospital - Medan from 1 May 2011 to 30 April 2016.Results: From 690 subjects intrathoracic malignancy, there were 137 (19.8%) patients with respiratory emergencies and mostly caused by lung tumors (83.9%). Massive MPE was is the most common emergency of 45 cases (6.5%) and massive haemoptysis of at least 4 cases (0.6%). The risk of death was higher in patients with respiratory emergencies. Mediastinum and location of tumor contribute in respiratory emergency appearance with respective OR of 3.9 and 1.5 (p value <0.005)Conclusions: Increased of mortality rate in patients with respiratory emergency and MPE massive is the most cases. Type of the malignancy and Right lung tumor contribute of respiratory emergency in intrathoracic malignancy cases.